Effect of silane treatment of carboxylic-functionalized multi-walled carbon nanotubes on the thermal properties of epoxy nanocomposites (eXPRESS Polymer Letters)
The effect of silane treatment of carboxylic-functionalized multi-walled carbon nanotubes (COOH-MWCNTs) on the thermal properties of COOH-MWCNTs/epoxy nanocomposites was studied by comparing the research results on differential scanning calorimetry and thermogravimetric analysis data of silane treated COOH-MWCNTs/epoxy system with those of as-received COOH-MWCNTs/epoxy system. At the initial curing stage, silane treatment of COOH-MWCNTs does not change the autocatalytic cure reaction mechanism of COOH-MWCNTs/diglycidyl ether of bisphenol-A glycidol ether epoxy resin/2-ethyl-4-methylimidazole (COOH-MWCNTs/DGEBA/EMI-2,4) system, however, silane treatment of COOH-MWCNTs has catalytic effect on the curing process, which could help to shorten pre-cure time or lower pre-temperature. Then, at the later curing stage, silane treatment of COOH-MWCNTs promotes vitrification, which would help to shorten post-cure time or lower post-temperature. Therefore, overall, silane treatment of COOH-MWCNTs could bring positive effect on the processing of epoxy nanocomposites. Furthermore, it was also found that silane treatment of COOH-MWCNTs does not affect the thermal degradation pattern of COOH-MWCNTs/DGEBA/EMI-2,4 system, however, decreases the thermal stability of COOH-MWCNTs/DGEBA/EMI-2,4 nanocomposites.